Efferocytosis induces a novel SLC program to promote glucose uptake and lactate release. (29th November 2018) - Morioka, Sho; Perry, Justin; Raymond, Michael; Medina, Christopher; Zhu, Yunlu; Zhao, Liyang; Serbulea, Vlad; Onengut-Gumuscu, Suna; Leitinger, Norbert; Kucenas, Sarah; Rathmell, Jeffrey; Makowski, Liza; et al.
Abstract Development and routine tissue homeostasis require a high turnover of apoptotic cells. These cells are removed by professional and non-professional phagocytes via efferocytosis1 . How a phagocyte maintains its homeostasis while coordinating corpse uptake, processing ingested materials and secreting anti-inflammatory mediators is incompletely understood1, 2 . Here, using RNA sequencing to characterize the transcriptional program of phagocytes actively engulfing apoptotic cells, we identify a genetic signature involving 33 members of the solute carrier (SLC) family of membrane transport proteins, in which expression is specifically modulated during efferocytosis, but not during antibody-mediated phagocytosis. We assessed the functional relevance of these SLCs in efferocytic phagocytes and observed a robust induction of an aerobic glycolysis program, initiated by SLC2A1-mediated glucose uptake, with concurrent suppression of the oxidative phosphorylation program. The different steps of phagocytosis2 —that is, 'smell' ('find-me' signals or sensing factors released by apoptotic cells), 'taste' (phagocyte–apoptotic cell contact) and 'ingestion' (corpse internalization)—activated distinct and overlapping sets of genes, including several SLC genes, to promote glycolysis. SLC16A1 was upregulated after corpse uptake, increasing the release of lactate, a natural by-product of aerobic glycolysis3 . Whereas glycolysis within phagocytes contributed to actin polymerization and the continued uptake of corpses, lactate released via SLC16A1 promoted the establishment of an anti-inflammatory tissue environment. Collectively, these data reveal a SLC program that is activated during efferocytosis, identify a previously unknown reliance on aerobic glycolysis during apoptotic cell uptake and show that glycolytic by-products of efferocytosis can influence surrounding cells. Distinct transcriptional programs are activated during different stages of apoptotic cell engulfment, including a unique program of genes coding for solute carrier proteins and enzymes in the glycolytic pathway.